2016
DOI: 10.1152/ajpendo.00213.2016
|View full text |Cite
|
Sign up to set email alerts
|

Does the muscle protein synthetic response to exercise and amino acid-based nutrition diminish with advancing age? A systematic review

Abstract: The precise role of age-related muscle anabolic resistance in the progression of sarcopenia and functional decline in older individuals is unclear. The present aim was to assess whether the muscle protein synthesis (MPS) response to acute exercise (endurance or resistance) and/or amino acid-based nutrition is attenuated in older compared with young individuals. A systematic review was conducted on studies that directly examined the influence of age on the MPS response to exercise and/or amino acid-based nutrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
81
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(92 citation statements)
references
References 115 publications
(247 reference statements)
0
81
1
1
Order By: Relevance
“…Eight of 21 studies showed significant differences between younger and older adults regarding the effects of protein or amino acid administration on muscle protein synthesis. The other 13 studies did not indicate a difference between younger and older subjects [34].…”
Section: Adults 65 Years Of Age and Oldermentioning
confidence: 85%
“…Eight of 21 studies showed significant differences between younger and older adults regarding the effects of protein or amino acid administration on muscle protein synthesis. The other 13 studies did not indicate a difference between younger and older subjects [34].…”
Section: Adults 65 Years Of Age and Oldermentioning
confidence: 85%
“…Anabolic resistance is the failure of normal anabolic stimuli to induce net protein synthesis. Such a response occurs, although by different mechanisms, in the elderly and in stressed ICU patients 9 , 10 . Primary drivers of anabolic resistance are thought to include splanchnic sequestration of amino acids, decreased availability of amino acids to muscle and possibly other organs, and a blunted anabolic response to the provision of amino acids 9 , 10 …”
Section: Protein Kinetics and Metabolic Effects Related To Disease Stmentioning
confidence: 99%
“…Recent reevaluations of the protein requirements with the use of the indicator amino acid oxidation technique suggest that nitrogen balance methodology may underestimate protein needs by as much as 30% (13,14). There is also evidence of anabolic resistance in the elderly, whereby skeletal muscle synthesis in response to ingested protein is suppressed at any given ingested dose, relative to younger individuals (15)(16)(17). With this uncertainty, protein intakes of up to twice the current RDA (2RDA) have been recommended as optimal for older adults at risk of sarcopenia (18).…”
Section: Introductionmentioning
confidence: 99%